2012
DOI: 10.1590/s1678-91992012000100016
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and risk factors associated with canine leptospirosis

Abstract: Leptospirosis is a globally distributed emerging zoonosis. Dogs are commonly affected and although other serovars can cause canine leptospirosis, Leptospira interrogans serovar Canicola is primary found in these animals. A retrospective study was conducted using a database of 1195 dogs tested for Leptospira infection from 2003 to 2010 at the Laboratory of Zoonosis Diagnosis at the Veterinary Hospital of São Paulo State University (UNESP) in Botucatu, São Paulo state, Brazil. The seroprevalence of infected dogs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
1
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 14 publications
1
8
1
5
Order By: Relevance
“…Therefore, environmental infection with leptospires was expected to be high, especially in relation to the Icterohaemorrhagiae serogroup. However, the results were contrary to this theory, and we can conclude that opossums have a low rate of infection in the region studied, despite occurrences of leptospirosis in Botucatu (Langoni et al, 2008;Coiro et al, 2012;Fornazari et al, 2012;Kikuti et al, 2012) and the presence of large populations of synanthropic rodents (personal communication from public health authorities). Because Leptospira DNA was found in opossum urine, this species may indeed act as a renal carrier of leptospirosis.…”
Section: Discussioncontrasting
confidence: 60%
See 1 more Smart Citation
“…Therefore, environmental infection with leptospires was expected to be high, especially in relation to the Icterohaemorrhagiae serogroup. However, the results were contrary to this theory, and we can conclude that opossums have a low rate of infection in the region studied, despite occurrences of leptospirosis in Botucatu (Langoni et al, 2008;Coiro et al, 2012;Fornazari et al, 2012;Kikuti et al, 2012) and the presence of large populations of synanthropic rodents (personal communication from public health authorities). Because Leptospira DNA was found in opossum urine, this species may indeed act as a renal carrier of leptospirosis.…”
Section: Discussioncontrasting
confidence: 60%
“…This study was conducted in the municipality of Botucatu (22°53′09″ S 48°26′42″ W), which is located in the center the state of São Paulo, the most populated and economically developed region of Brazil. Previous studies have confirmed that Leptospira infection occurs widely in several domestic species in this region (Langoni et al, 2008;Coiro et al, 2012;Fornazari et al, 2012;Kikuti et al, 2012). Botucatu has a population of approximately 140,000 habitants, annual rainfall of 1358 mm, annual mean temperature of 20.7°C, intensive land use for eucalyptus plantations, agriculture and livestock, massive fragmentation of native forest and atypical strong winds (CEPAGRI; IBGE).…”
Section: Methodsmentioning
confidence: 77%
“…In Yucatan, Mexico, the serovars present are Canicola and Icterohaemorrhagiae (Jimenez-Coello et al, 2008). In Sao Paulo, Brazil, the seroprevalence in dogs is 20.08%, and the most prevalent serovars are Canicola (6.7%), Copenhageni (5.0%), Icterohaemorrhagiae (2.9%), Autumnalis (2.9%), Pyrogenes (2.8%), Pomona (2.0%), Hardjo (2.0%), Australis (1.8%), Bratislava (1.6%), Cynopteri (1.4%), Grippotyphosa (1.3%) and Djasiman (1.0%) (Kikuti et al, 2012). Although an animal was considered as positive to leptospirosis when the antibodies titers were equal to or greater than 100, the presence of dogs with an antibody response at titers 1:50 for different serovars might indicate the exposure to the bacteria via contact with other animals that act as reservoirs for these serovars, such as rats and mice (serovars Icterohaemorrhagiae and Grippotyphosa).…”
Section: Resultsmentioning
confidence: 99%
“…Leptospirosis is a zoonotic infectious disease of worldwide distribution that is endemic in tropical and temperate climates, with higher prevalence in tropical countries (Levett, 2001;Adler and de la Peña, 2010;Desvars et al, 2011). Leptospirosis affects humans, domestic and wild animals (Båverud et al, 2009), and the reservoirs are wild or domestic animals such as rodents, cattle or dogs (Kikuti et al, 2012). In urban areas, rodents (mostly rats) are the main carriers of the disease (Oliveira et al, 2012), whereas the dog is considered a dead-end host (Prescott, 2008;Reis et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Personas que están expuestas laboralmente a aguas estancadas, labores agrícolas, personal veterinario, ganaderos e inspectores de carne, presentan un alto riesgo de exposición; sin embargo esto depende de las buenas prácticas de bioseguridad que se lleven a cabo durante el contacto con animales portadores o lugares donde pueda encontrarse la bacteria (Kikuti et al, 2012) Tendencias en el campo de conocimiento. Entre 1960 a 2015, de 121 artículos que fueron publicados en el tema; se tiene que 11 artículos corresponden a reportes realizados en Colombia, 8 a Argentina, 11 artículos en Centroamérica, 2 para Chile, 1 a Ecuador, 12 en Perú y 1 a Venezuela; los restantes corresponden a información general acerca de la bacteria y su epidemiología.…”
Section: Factores De Riesgo Asociados a La Enfermedad En Humanosunclassified